Methods of the passenger`s functional state research - Sotnikova, Anna (Видавництво Львівської політехніки, 2017)
The research of the functional state (FS) of the passenger is important for assessing the quality of service of transportation by public transport. Analyzed techniques can be used during research of human’s FS. The advantages and disadvantages of different methods of evaluation of FS are established.
Keywords: functional state; psychological and physiological parameters; electrocardiogram; heart rate variability; RSA index